Grain size effect on the critical behavior of the ferromagnetic transition in electronically phase separated La0.5Ca0.5MnO3 - Abate, Nicolás Bruno; Toro, J.; Polla, G.; Irurzun, I.; Passanante, Sebastian Eduardo; Vega, D.; Granja, Leticia Paula; Quintero, Mariano Horacio (Elsevier, 2023)
Fil: Abate, Nicolás Bruno. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Física de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Física de Buenos Aires; Argentina